In ovo electroporation of chicken limb bud ectoderm: Electroporation to chick limb ectoderm. Issue 9 (3rd May 2021) - Tomizawa, Reiko Rachel; Tabin, Clifford James; Atsuta, Yuji
Abstract: Background: Deciphering how ectodermal tissues form, and how they maintain their integrity, is crucial for understanding epidermal development and pathogenesis. However, lack of simple and rapid gene manipulation techniques limits genetic studies to elucidate mechanisms underlying these events. Results: Here we describe an easy method for electroporation of chick limb bud ectoderm enabling gene manipulation during ectoderm development and wound healing. Taking advantage of a small parafilm well that constrains DNA plasmids locally and the fact that the limb ectoderm arises from a defined site, we target the limb ectoderm forming region by in ovo electroporation. This approach results in focal and efficient transgenesis of the limb ectodermal cells. Further, using a previously described Msx2 promoter, gene manipulation can be specifically targeted to the apical ectodermal ridge (AER), a signaling center regulating limb development. Using the electroporation technique to deliver a fluorescent marker into the embryonic limb ectoderm, we show its utility in performing time‐lapse imaging during wound healing. This analysis revealed previously unrecognized dynamic remodeling of the actin cytoskeleton and lamellipodia formation at the edges of the wound. We find that the lamellipodia formation requires activity of Rac1 GTPase, suggesting its necessity for wound closure. Conclusion: Our method is simple and easy. Thus, it would permit high throughput tests for gene function during limb ectodermal development and wound healing. Key Findings: We have developed a simple and easy electroporation method for gene manipulation in chick limb ectoderm by taking advantage of a parafilm, a cheap and common lab material.